The Effect Of E-Service Quality And Perceived Value On Customer Satisfation On The Use Of The Halodoc Application In Medan City - Khofifah Aini; Hafiza Adlina (SEAN Institute, 2023)
The purpose of this study was to determine the effect of e-service quality and perceived value on customer satisfaction on the use of the Halodoc application in the city of Medan. This research is a quantitative study with an associative approach and uses data collection methods using questionnaire survey instruments and non-probability sampling techniques. The sample of this research is 100 respondents who have used the Halodoc application service at least twice and are domiciled in the city of Medan. This study processes data and research results using SPSS software version 26. Based on the results of research that has been carried out, it shows that e service quality significantly effect on customer satisfaction with t value of 2.927 > t table 1.984, perceived value significantly effect on customer satisfaction with t value 8,489 > t table 1,984, e service quality and perceived value significantly effect on customer satisfaction simultaneously with f value of 73.290 > f table 3.09.